Mechanisms Underlying CD4+ Treg Immune Regulation in the Adult: From Experiments to Models - Caridade, Marta; Graca, Luis; Ribeiro, Ruy M. (Frontiers in Immunology, 2013)
To maintain immunological balance the organism has to be tolerant to self while remaining competent to mount an effective immune response against third-party antigens. An important mechanism of this immune regulation involves the action of regulatory T-cell (Tregs). In this mini-review, we discuss some of the known and proposed mechanisms by which Tregs exert their influence in the context of immune regulation, and the contribution of mathematical modeling for these mechanistic studies. These models explore the mechanisms of action of regulatory T cells, and include hypotheses of multiple signals, delivered through simultaneous antigen presenting cell (APC) conjugation; interaction of feedback loops between APC, Tregs and effector cells; or production of specific cytokines that act on effector cells. As the fields matures, and competing models are winnowed out, it is likely that we will be able to quantify how tolerance-inducing strategies, such as CD4-blockade, affect T-cell dynamics and what mechanisms explain the observed behavior of T-cell based tolerance.